Law and Democracy in Contemporary India Constitution, Contact Zone, and Performing Rights - Yamamoto, Tatsuya; Ueda, Tomoaki (Human Rights Interventions, 2019)
This book analyses legal orders, actors and democracy in contemporary India, with a particular focus on the everyday contexts and dynamics of human rights, citizenship and socio-economic rights and laws. The contributions explore both 'institutionalization from above', where the judiciary and legislative body aim to govern people, and 'institutionalization from below', where the governed attempt to expand their substantive rights embedded within their everyday lives. This analysis identifies contact zones between the two directions, which act as spaces for democratic participation and negotiation. Such a perspective should be useful to both those who are interested in Indian politics, and anthropologists and sociologists working on dynamics of laws and rights.